Antiproliferative effect of methyl-beta-cyclodextrin in vitro and in human tumour xenografted athymic nude mice. - Grosse, P. Y. (Nature Publishing Group|1, 1998)
The anti-tumour activity of methyl-beta-cyclodextrin (MEBCD), a cyclic oligosaccharide known for its interaction with the plasma membrane, was investigated in vitro and in vivo and compared with that of doxorubicin (DOX) in the human tumour models MCF7 breast carcinoma and A2780 ovarian carcinoma. In vitro proliferation was assessed using the MTT assay. In vivo studies were carried out using xenografted Swiss nude mice injected weekly i.p. with MEBCD at 300 or 800 mg kg(-1) or DOX at 2 mg kg(-1), during 2 months. Under these conditions, MEBCD was active against MCF7 and A2780 cell lines and tumour xenografts. For each tumour model, the tumoral volume of the xenografted mice treated with MEBCD was at least twofold reduced compared with the control group. In the MCF7 model, MEBCD (800 mg kg(-1)) was more active than DOX (2 mg kg(-1)). After 56 days of treatment with MEBCD, no toxicologically meaningful differences were observed in macroscopic and microscopic parameters compared with controls. The accumulation of MEBCD in normal and tumour tissues was also assessed using a chromatographic method. Results indicated that after a single injection of MEBCD, tumour, liver and kidneys accumulated the highest concentrations of MEBCD. These results provided a basis for the potential therapeutic application of MEBCD in cancer therapy.